"Probleme des Klassenkampf" im Betrieb - Zeuner, Bodo (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1995)
The artide presents a review of the class struggle debates in PROKLA up to the 80s (which were then interrupted) as well as more recent approaches of class analysis. The review shows that class and class struggle cannot be examined without a political analysis. However, a political analysis of modern societies, in opposition to the trend prevailing today, is not sufficiently informed without a class analysis, because an abstraction from class interrelations in capitalism is not possible.